Hedge Funds & The Alpha Paradigm - Logothetis, Ioannis (2012)
Numerous heavily quantitative strategies, macroeconomic and esoteric investment techniques involving currencies, fixed income products, commodities and equities have proven to be very profitable over the last two decades as math whizzes of Wall Street implemented mathematical and quantum physics models to outperform financial markets in search of Alpha. The development of mathematical algorithms, exotic trading techniques, lightening fast computerized machines and platforms and the effective in-depth skilful macroeconomic analysis from numerous hedge fund managers have resulted in trillions of profits or even losses which have in turn affected the global financial system significantly. This thesis will examine the features of the hedge fund industry focusing on the analysis and the background of the ‘Alpha’ paradigm, the various profitable strategies on record, their performance over the years, the recent developments in the field, their influence and their effects on the global economy and the financial system with the infamous events of 2007-2008 serving as a backdrop. By assessing historically the hedge fund performance it could be demonstrated that hedge funds produce superior risk-adjusted returns over time comparing with traditional assets, and they carried fewer risks when the volatilities are compared. Our findings also support that hedge funds possess the ability create alpha consistently and systematically with limited volatility and by outperforming traditional asset classes, while there is a limited interaction between hedge fund returns and systematic market factors.